Educational profile of the illiterate population in Rio Grande do Norte in 2010 (Research, Society and Development, 2021)
This article emphasizes the problem of illiteracy in the State of Rio Grande do Norte - RN, highlighting population variables in their social context. Countless factors are contributing to school dropout, the lack of new teaching methodologies, as well as specific attention to each social type of student has increased illiteracy rates in recent years. The objective of this work is to expose many of the factors that cause the evasion of the student from the school, in its many variables exposed here, illiteracy is a worldwide problem, and must be combated with the elaboration of many education projects and try to extend education by all over the national territory, the present work also helps public authorities to be aware of how serious the issue involved here is, illiteracy in Brazil. This research was developed in a descriptive and retrospective way from the year 2010, with data provided and extracted from the DATASUS database. The variables assessed in the discussion were: rate of illiterate people, collected in 2010, municipalities with registered illiterate person rates, age group of illiterate people living in registered municipalities and the area of ​​residence of these illiterate people. Economic, political and social factors are decisive in the life of the population, as they will decide who will have access to and access to education, this dynamic that always presents inequality in the distribution of financial resources has put the education of Brazilians in check.